Reconstructing The Regulation Of The Empty Box In Single-Candidate Pilkada Based On Electoral Law Justice - Moh. Maskurudin Hafid (CV. AFDIFAL MAJU BERKAH, 2026)
The phenomenon of regional elections with a single candidate in Indonesia continues to increase and raises serious problems for the quality of local democracy. The Constitutional Court Decision Number 100/PUU-XIII/2015 has provided constitutional legitimacy for